Association Models for Binding of Molecules to Nanostructures - Lissi-Gervaso, E (Royal Society of Chemistry, 2017)
The interaction between nanoparticles and molecules plays a key role in determining the activity and performance of a given nanostructure. These interactions are pivotal for a variety of applications including drug delivery, surface manipulation for targeted therapies, and catalysis. However, to this day, gathering precise association parameters for the interaction of the molecules with nanostructures remains elusive and mostly imprecise. In this review, we present a critical discussion of the most commonly used techniques and models intended for determining the association of molecules with nanoparticles. Particular emphasis has been put on discussing the limitations and pitfalls related to determining association constants in this tutorial review. © 2017 The Royal Society of Chemistry.